2015
DOI: 10.1186/s12917-015-0323-y
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of Chlamydia abortus infection in free-ranging white yaks in China

Abstract: BackgroundChlamydia is gram-negative obligate bacteria which causes a wide variety of diseases in humans and animals. To date, there are a few reports about the seroprevalence of Chlamydia and the risk factors associated with Chlamydia infection in yaks in the world. In this study, 974 blood samples were collected from white yaks (Bos grunniens) in Tianzhu Tibetan Autonomous County, Gansu province, northwest China from June 2013 to April 2014.ResultsAntibodies against Chlamydia abortus were examined by the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…A number of health measures, including foot and joint pathologies [10, 21, 25, 33–35], the presence of wounds and skin lesions [22, 23, 36], and discrete assessments by body region [24], have been used as indicators of elephant well-being under human care, but until now, no studies have assessed the total number of active clinical events during a specific period of time as a potential welfare indicator. Rather than using discrete health assessments [23, 24], surveys sent to veterinarians [25, 37], or a review of causes of morbidity and mortality [21], we created variables based on the total number of clinical events recorded within the 12-month study period of the EWP. Analyses of over 1100 clinical events in 220 elephants revealed that certain pathologies (e.g., gastrointestinal issues, skin lesions, lameness/stiffness, and foot pathologies) varied by species, sex, and age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of health measures, including foot and joint pathologies [10, 21, 25, 33–35], the presence of wounds and skin lesions [22, 23, 36], and discrete assessments by body region [24], have been used as indicators of elephant well-being under human care, but until now, no studies have assessed the total number of active clinical events during a specific period of time as a potential welfare indicator. Rather than using discrete health assessments [23, 24], surveys sent to veterinarians [25, 37], or a review of causes of morbidity and mortality [21], we created variables based on the total number of clinical events recorded within the 12-month study period of the EWP. Analyses of over 1100 clinical events in 220 elephants revealed that certain pathologies (e.g., gastrointestinal issues, skin lesions, lameness/stiffness, and foot pathologies) varied by species, sex, and age.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive weight and lack of exercise may also contribute to some of these problems [21]. Other conditions, such as foot and joint health [10], injuries [22], and skin lesions [23], could be directly related to extrinsic conditions; and the ability of an individuals’ immune system to combat disease is central to etiopathogenesis. Understanding how different aspects of the captive environment impact health status would be beneficial to overall well-being, and may also aid in our understanding of susceptibility to disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, the PCR-RFLP method was developed and used only to identify Chlamydia species isolated from animals ( 11 ), while recombinase polymerase amplification (RPA) was used to identify C. abortus ( 98 ). However, IHA is considered as a simple, safe, and reliable means of testing C. abortus antibodies, and has been employed in previous serological investigations ( 79, 99 ).…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Chlamydia abortus is the causative agent of abortion and foetal loss in cattle in arctic-alpine areas in China and other countries (Merdja et al 2015;Qin et al 2015). Additionally, C. abortus has also been reported as a zoonotic pathogen because it can also result in abortion in humans (Psarrakos et al 2011;Campos-Hernández et al 2014).…”
Section: Introductionmentioning
confidence: 97%